QbD Consideration for Developing a Double-Layered Tablet into a Single-Layered Tablet with Telmisartan and Amlodipine - Kim, Joo Eun; Park, Young Joon (Pharmaceutics, 2022)
The aim of this study was to develop a single-layered version of commercially available Twynstar® (Telmisartan + Amlodipine) double-layered tablets to improve the dosing convenience. A quality-by-design approach was applied to develop the single-layered version. To evaluate the range and cause of risks for a single-layered tablet in the formulation design research, we used the tools of the risk assessment, initial risk assessment of preliminary hazard analysis and main risk assessment of failure mode and effect analysis to determine the parameters affecting formulation, drug dissolution, and impurities. The critical material attributes were the stabilizer and disintegrant, and the critical process parameters were the wet granulation and tableting process. The optimal range of the design space was determined using the central composite design in the wet granulation and tablet compression processes. The stabilizer, kneading time, and disintegrant of the wet granulation were identified as X values affecting Y values. The compression force and turret speed in the tablet compression were identified as X values affecting Y values. After deciding on the design space with the deduced Y values, the single-layered tablets were formulated, and their dissolution patterns were compared with that of the double-layered tablet. The selected quality-by-design (QbD) approach single-layered tablet formulated using design space were found to be bioequivalent to the Twynstar® double-layered tablets. Hence, the development of single-layered tablets with two API using the QbD approach could improve the medication compliance of patients and could be used as a platform to overcome time-consuming and excessive costs and the technical and commercial limitations related to various multi-layered tablets.
Keywords: Amlodipine; Bioequivalence; Design of experiment; Design space; Quality-by-design; Risk assessment; Telmisartan